2022
DOI: 10.1183/23120541.00212-2022
|View full text |Cite
|
Sign up to set email alerts
|

Role of digital health in pulmonary rehabilitation and beyond: shaping the future

Abstract: Pulmonary rehabilitation (PR) is a cost-effective intervention with well-known benefits on exercise capacity, symptoms and quality of life in patients with chronic respiratory diseases. Despite the compelling evidence of its benefits, PR implementation is still suboptimal, and maintenance of PR benefits is challenging. To overcome these pitfalls, there has been a growing interest to develop novel models for PR delivery. Digital health is a promising solution, as it has the potential to address some of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 104 publications
0
3
0
1
Order By: Relevance
“…This aligns with the long-established role of pulmonary rehabilitation in managing chronic respiratory conditions [24]. Additionally, the role of telecoaching in enhancing the effects of homebased pulmonary rehabilitation programs is notable, especially considering the importance of remote healthcare delivery in the ongoing pandemic scenario [25]. However, more highquality studies are needed to assess the longterm effects and the optimal duration of these interventions.…”
Section: Fig 1 Prisma Flowchart Depicting the Study Selection Processmentioning
confidence: 62%
“…This aligns with the long-established role of pulmonary rehabilitation in managing chronic respiratory conditions [24]. Additionally, the role of telecoaching in enhancing the effects of homebased pulmonary rehabilitation programs is notable, especially considering the importance of remote healthcare delivery in the ongoing pandemic scenario [25]. However, more highquality studies are needed to assess the longterm effects and the optimal duration of these interventions.…”
Section: Fig 1 Prisma Flowchart Depicting the Study Selection Processmentioning
confidence: 62%
“…Örneğin; Japonya telekomünikasyon ağları aracılığıyla, yaşlıların evlerinde elde ettiği yaşamsal verileri tıbbi kurumlara bağlamaktadır. Bu sayede, kullanıcılar yaşam tarzlarını koruyarak daha kısa sürelerde tedavi edilmekte, bu ise sonuç olarak sadece tıp merkezleri için değil, hastalar için de maliyetlerin azaltılmasına izin vermektedir 12 13 . Özel hastanelerin dijitalleşme süreci ile ilgili yönetici görüşlerinin ortaya çıkarılması amacıyla yapılan başka bir nitel araştırma sonucunda da hastanelerin dijitalleşmesinin, her türlü verinin elektronik olarak kaydedilmesi, veri güvenliğinin sağlanması, Sağlık Bilgi Sistemine ve güncel son teknoloji cihazlara sahip olma şeklinde güçlü yanları olduğu belirlenmiştir 18 .…”
Section: Discussionunclassified
“…However, recent guidelines support the development of home-based PR, telehealth, and mHealth interventions in which objective, timely, and reliable monitoring of treatment implementation is deemed important. Remote technologies and wearable activity trackers could strengthen contact with patients, increase participation rates, and long-term adherence to healthy behaviors (34). Furthermore, although the digital literacy of patients with COPD is considered a barrier to PR participation, data from a recent study revealed encouraging results with the successive use of smartphones and wearable technology by an older respiratory population (35).…”
Section: Discussionmentioning
confidence: 99%